The evolution patterns of active functional groups and reaction pathways during the low-temperature oxidation process of coal - CHEN Xiangyuan; LIU Xingyu; YAO Yutong; ZHAO Zining (矿业科学学报)
This study employed the in-situ infrared experiment (In-situ FTIR) to investigate the content changes of key active functional groups during the low-temperature oxidation process so as to obtain the transformation patterns between functional groups. Based on the quantum chemistry theory, we conducted structural optimization, transition state configuration analysis, thermodynamic parameter calculations and intrinsic reaction coordinate (IRC) computations on the constructed coal molecular models by using GaussView 6.0 and Gaussian 16. This serves for a comprehensive understanding of the evolution patterns and reaction pathways of active functional groups during coal low-temperature oxidation at both macroscopic and microscopic levels. Results reveal that —CH3, —CH2— in coal could transform into oxygen-containing functional groups such as —CHO, —COOH, —OH during low-temperature oxidation. The reactions of key active functional groups in coal with O2 were found to be endothermic, requiring external heat input, while those with ·OH were exothermic, albeit initial dependance on the original ·OH in coal. This research contributes to the further understanding of the mechanism underlying low-temperature oxidation of coal.